2023
DOI: 10.1159/000529801
|View full text |Cite
|
Sign up to set email alerts
|

Skin Tests versus Serology: Specific IgE May Suffice for Diagnosis of Vespid Venom Allergy and Follow-Up of Allergen Immunotherapy

Abstract: <b><i>Introduction:</i></b> In adults, allergic reactions to insect stings are among the most frequent causes of anaphylaxis, a potentially life-threatening condition. Recurrent anaphylaxis following vespid stings may be prevented by allergen immunotherapy (AIT). The aim of this study was to evaluate the benefit of measuring venom-induced wheal area in intracutaneous skin tests (ICT), in comparison to various serological and clinical parameters, for the diagnosis of severe vespid venom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…However, definitive diagnosis of allergy would require nasal or conjunctival allergen challenge. Nonetheless, recent studies have shown that IgE levels are a good indicator of underlying allergies and may even be superior to SPT [33,34]. Moreover, the strengths of the study at hand are the well documented and characterized individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, definitive diagnosis of allergy would require nasal or conjunctival allergen challenge. Nonetheless, recent studies have shown that IgE levels are a good indicator of underlying allergies and may even be superior to SPT [33,34]. Moreover, the strengths of the study at hand are the well documented and characterized individuals.…”
Section: Discussionmentioning
confidence: 99%